Station for Experimental Evolution at Cold Spring Harbor Laboratory on Long Island, New York - Unknown (2024)
Glass lantern slide showing the Station for Experimental Evolution and biological lab at the Cold Spring Harbor Laboratory on Long Island, New York. Photo taken from the east side of the harbor.